Psychological Variables Related to Adaptation to the COVID-19 Lockdown in Spain - Morales-Vives, Fabia; Dueñas, Jorge-Manuel; Vigil-Colet, Andreu; Camarero-Figuerola, Marta (Frontiers in Psychology, 2020)
Recent studies show that quarantine and lockdown are effective measures for controlling COVID-19 outbreaks, but may be an unpleasant experience with psychological consequences. For this reason, the main aim of this study was to determine which personal sociodemographic and psychological variables are related to adapting to lockdown in a Spanish population. Questionnaires were administered to 2055 individuals (60.7% women) who were resident in Spain and aged between 18 and 80 years old. We also administered some items related to feelings and behaviours during lockdown. The results showed that sex and age are variables to be taken into account. In fact, women tended to show greater stress, a more pessimistic attitude, and lower self-esteem. However, older people adapted better to lockdown although they were also more worried. Married people also adapted better although they too were more worried. The results also showed that more resilient people, with higher subjective happiness and life satisfaction, develop strategies for adapting positively to adversity, and tend to adapt better to lockdown, with more positive attitudes and behaviors. In terms of personality traits, higher neuroticism and lower extraversion were related to worse adaptation to lockdown. This study also showeds that lockdown has had a negative psychological impact on those people who did not adapt well to the situation and the changes during the first four weeks of lockdown.